Organomediated approaches to 18F-radiochemistry for PET - Buckingham, F (2015)
This thesis has focussed on 18F-fluorination reactions activated by an organomediator, with the aim of broadening the scope of metal-free reactions in 18F-radiosynthesis. Chapter 1 provides an introduction to positron emission tomography (PET) and 18Fradiochemistry, including radioisotope production and modes of activation in 18Fradiosynthesis. In Chapter 2, the concept of chirality and its relevance in the context of radiotracer design is introduced. The previously disconnected fields of organomediated asymmetric fluorination and 18F-radiosynthesis are merged for the first time via investigation of three distinct activation modes: chiral non-racemic secondary amine-mediated asymmetric α-18F-fluorination of aldehydes employing [18F]N-fluorobenzenesulfonimide; use of a phase transfer reagent for asymmetric 18F-fluorocyclisation and application of a chiral nonracemic 18F-fluorinating agent, chiral [18F]Selectfluor bis-triflate. Application of the first of these approaches to the radiosynthesis of the PET tracer (2S,4S)-4-[18F]fluoroglutamic acid with high d.r. is described. Chapter 3 explores the use of hypervalent iodine reagents to mediate the oxidative fluorination of N-arylsulfonamides with nucleophilic fluoride via an umpolung approach. Preliminary studies on translation to radiosynthesis with [18F]fluoride are also disclosed. In Chapter 4, experimental data is provided for all compounds, as well as analytical and chiral HPLC traces for 18F-reactions.